Performance Evaluation of a 4 × 20-Gbps OFDM-Based FSO Link Incorporating Hybrid W-MDM Techniques - Singh, Mehtab; Chebaane, Saleh; Ben Khalifa, Sana; Grover, Amit; Dewra, Sanjeev; Angurala, Mohit (Frontiers in Physics, 2021)
Free space optics (FSO) has been envisioned as an crucial technique to meet the high-bandwidth requirements in future wireless information transmission links and a feasible solution to the last-mile bottleneck problem as a result of its merits that include high-speed data transportation, secure and low latency networks. Due to these merits, FSO is a reliable technology for future healthcare and biomedical services like transmission of biomedical sensor signals. This research work reports the designing and simulative evaluation of the performance of high-speed orthogonal frequency division multiplexing-based free space optics link by incorporating wavelength division multiplexing of 2 independent frequency channels (193.1 THz and 193.2 THz) along with mode division multiplexing of distinct spatial laser Hermite Gaussian modes (HG01 and HG03). 4 independent 20 Gbps quadrature amplitude modulated data signals are transported simultaneously under different atmospheric weather conditions using the proposed link. Also, the link performance has been investigated for increasing beam divergence angle.